The Transformational Leadership of The Principal in Fostering a Collaborative Culture Among Educators at State Senior High School 1 Percut Sei Tuan - Hasibuan, Irma Tussa’diyah; yusuf, Yusuf Hadijaya (Graduate Program Magister Manajemen Pendidikan, 2025)
This study aims to describe the role of the principal's transformational leadership in forming a collaborative culture among educators at SMA Negeri 1 Percut Sei Tuan. The background of this study is based on the importance of teacher collaboration to improve the quality of education and the role of leaders who encourage positive change. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation from the principal, teachers, and students. The results showed that the principal implemented transformational leadership principles, such as teacher empowerment, building a shared vision, and creating a collaborative environment. The strategies used included the formation of the MGMP community, regular meetings, open communication, and support for teacher innovation. This study also found that educators' internal motivation and communicative leadership were key to creating a sustainable collaborative culture. These findings contribute significantly to the development of more adaptive and participatory education management.